Women's International League for Peace and Freedom At Courthouse Transit Stop Protesting Removal From Buses Their "Think Before You Register For The Draft" Signs - Watkins, Howard::::::::: (1982)
Protesters holding banner and banned signs; Front row: ?, Pam Whalen, ?, Ernestine Leas in sunglasses, Louise Erickson in black and white dress, Geneva Bennett (brown hair), Bob Fischer, Lindell Cross, Barbara Gaines, Carol Fisher, Evo Bluestein; Back Row: ???, Mariah Bennett, Cindy Calvert, Nancy Marsh looking left, Raine Iyall, Dakota Iyall, Sandra Iyall, Patrick Young Several protesters holding banned posters; Lloyds Bank sign in background at Fresno and Van Ness